2015
DOI: 10.1016/j.apal.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cone avoidance and randomness preservation

Abstract: Let X be an infinite sequence of 0's and 1's. Let f be a computable function. Recall that X is strongly f -random if and only if the a priori Kolmogorov complexity of each finite initial segment τ of X is bounded below by f (τ ) minus a constant. We study the problem of finding a PAcomplete Turing oracle which preserves the strong f -randomness of X while avoiding a Turing cone. In the context of this problem, we prove that the cones which cannot always be avoided are precisely the K-trivial ones. We also prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To define the notions of negligibility and non-negligibility, we need to review the definition of left-c.e. semi-measures, which were initially introduced by Solomonoff [29, 30] and first systematically studied by Levin and Zvonkin [20].…”
Section: Negligibility and Non-negligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…To define the notions of negligibility and non-negligibility, we need to review the definition of left-c.e. semi-measures, which were initially introduced by Solomonoff [29, 30] and first systematically studied by Levin and Zvonkin [20].…”
Section: Negligibility and Non-negligibilitymentioning
confidence: 99%
“…To prove Theorem 1.2, we prove a strengthening of Theorem 6.1 in terms of a family of weak notions of randomness; just as Theorem 1.1 follows from Theorem 6.1, so too will Theorem 1.2 follow from this strengthening. The following notion was explicitly defined by Higuchi et al [11] and was further studied by Simpson and Stephan [27]. Definition 6.7.…”
Section: A New Application Of the Techniquementioning
confidence: 99%
“…Kjos‐Hanssen, Merkle, and Stephan [12] showed that every C‐compression function is PA‐complete. Stephan and Simpson [19] gives yet another characterization of K‐trivials (reals of which all initial segments have the lowest possible Kolmogorov complexity) as the reals computable in every PA degree and relative to which the c.e. random real normalΩ is still 1‐random.…”
Section: Introductionmentioning
confidence: 99%